Predictive factors for special care units admission and in-hospital mortality of geriatric patients that presented to red zone of the Emergency Department of Hospital Universiti Sains Malaysia - Yen, Lim Khai (2018)
Introduction: The objective of this study aimed to determine the prevalence of geriatric patients being treated in Red Zone of Emergency Department in Hospital Universiti Sains Malaysia (USM), and factors associated with special care unit admission and in-hospital mortality. Methodology: This study was a single centre prospective cross-sectional study which was carried out from 1 January 2016 – 31 December 2016 at Red Zone of the Emergency Department Hospital USM. All patients aged 60 years and above were included. Systematic random sampling was used. Variables were analyzed using simple and multiple logistic regressions. Results: Total patients included in this study were 328 patients, 55.8% were male and 91.2% were Malay. The mean age was 70.6 years old. The cases geriatric patients commonly presented were cardiovascular (31.4%), infectious disease (29.6%), neurology (14.9%), and respiratory (12.5%). Out of 328 patients studied, 187 patients (57.0%) were admitted to general wards, 110 patients (33.5%) were admitted to SCU. 55 patients (16.8%) passed away within the period of in-hospital treatment. Factors associated with SCU admissionwere the usage of NIV, and the usage of inotropic support. On the other hand, factors associated with in-hospital mortality were blood urea level, serum albumin level and the application of mechanical ventilation. Conclusions: Geriatric patients who presented to Red Zone of ED requiring ventilator and inotropic support had shown to have worse outcome. The associated factors for SCU admission and in-hospital mortality had been identified, and this will enable better settings cater to the needs for critically ill geriatric patients.